“Smart-Bung” Pengembangan Media Pembelajaran Pada Teknik Dasar Bulutangkis - Debian Solekhudin (Journal of Physical Activity and Sports (JPAS), 2022)
This research is motivated by the lack of interesting learning media innovations that exist for learning PJOK, especially about basic badminton techniques and the difficulty of some students in understanding the basic badminton techniques taught in schools due to the lack of student interest in learning PJOK, especially badminton when in class or learning theory. . This study aims to develop a learning application for the basic techniques of badminton "smart-bung" for high school / vocational high school students around the world. This research is a research development or Research and Development (R&D) which uses the ADDIE development model. There are 5 stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation, Product validation is carried out by material experts and experts. media. Media. then developed and tested the feasibility of the product to the teacher and 106 students of class XI AKL SMKN 9 Semarang. The results of the descriptive analysis of the percentage of data showed that the questionnaire of material experts and instructional media experts was 83% with the category "suitable for use without revision". The results of the teacher response questionnaire analysis were 89% with the category "very feasible to use". The results of the student response questionnaire analysis were 94% with the category "very feasible to use".